2015
DOI: 10.9758/cpn.2015.13.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scopolamine Butylbromide on Clozapine-induced Hypersalivation in Schizophrenic Patients: A Case Series

Abstract: Clozapine has been demonstrated to be useful for treating refractory schizophrenia. However, hypersalivation occurs in 31.0–97.4% of the patients treated with clozapine. Accordingly, some patients who are disturbed by their hypersalivation refuse to continue with clozapine treatment. This study investigated the efficacy of the anticholinergic agent scopolamine butylbromide against clozapine-induced hypersalivation. Five schizophrenia patients were coadministered scopolamine butylbromide (30–60 mg/day) for 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“… 17 , 18) It usually develops early in the course of treatment. Previous reports have indicated that scopolamine 19) and scopolamine butylbromide 20) (anticholinergic agents) are effective against hypersalivation. However, the treatment of hypersalivation remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18) It usually develops early in the course of treatment. Previous reports have indicated that scopolamine 19) and scopolamine butylbromide 20) (anticholinergic agents) are effective against hypersalivation. However, the treatment of hypersalivation remains incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed no significant difference in DSFS scores between anti-cholinergic users and non-users in our clinical study. Anti-cholinergic drug users were taking biperiden or scopolamine butylbromide, which are reportedly effective against CIS (Liang et al, 2010;Takeuchi et al, 2015). This result may be attributed to the fact that most anti-cholinergic drug users took the drug during the day, which might have been less effective against nocturnal sialorrhea.…”
Section: )mentioning
confidence: 99%
“…However, future development of a patch should use SBB rather than scopolamine due to the reduced side effects of SBB. 7…”
Section: Adsorption and Release Of Sbbmentioning
confidence: 99%
“…However, different from scopolamine, SBB cannot cross the blood-brain barrier, and therefore does not cause undesired effects in central nervous system. 7 The administration of scopolamine or SBB can be orally, intravenous or transdermal. According to Brown and Laiken, 8 scopolamine can be absorbed effectively when applied transdermal in the retroauricular region, where the major salivary gland is located.…”
Section: Introductionmentioning
confidence: 99%